Uncorking the limitation—improving dual tasking using transcranial electrical stimulation and task training in the elderly: a systematic review - Jiang, Yong; Ramasawmy, Perianen; Antal, Andrea (Frontiers in Aging Neuroscience, 2024)
Introduction With aging, dual task (DT) ability declines and is more cognitively demanding than single tasks. Rapidly declining DT performance is regarded as a predictor of neurodegenerative disease. Task training and non-invasive transcranial electrical stimulation (tES) are methods applied to optimize the DT ability of the elderly. Methods A systematic search was carried out in the PUBMED, TDCS (transcranial direct current stimulation) databases, as well as Web of Science, and a qualitative analysis was conducted in 56 included studies. Aiming to summarize the results of studies that implemented tES, task training, or the combination for improving DT ability and related performance changes in healthy elderly and geriatric patients. For different approaches, the training procedures, parameters, as well as outcomes were discussed. Results Task training, particularly cognitive-motor DT training, has more notable effects on improving DT performance in the elderly when compared to the neuromodulation method. Discussion Anodal transcranial direct current stimulation (tDCS) over the left dorsolateral prefrontal cortex (L-DLPFC), or its combination with task training could be promising tools. However, additional evidence is required from aged healthy people and patients, as well as further exploration of electrode montage.